ANALYZING STUDENT’S TEXT WITHIN CRITICAL THINKING, CRITICAL LITERACY, AND APPRAISAL THEORY FRAMEWORKS “DANGERS OF TEXTING WHILE DRIVING” - Anna Riana Suryanti Tambunan; Widya Andayani; Winda Setiasari; Fauziah Khairani Lubis (State University of Medan, 2019)
This paper is entitled